Early‐life exposure to low levels of permethrin exerts impairments in learning and memory with the effects on neuronal and glial population in adult male mice. Issue 12 (15th August 2019) - Saito, Hirokatsu; Hara, Kenshiro; Tominaga, Takashi; Nakashima, Kinichi; Tanemura, Kentaro
Abstract: Permethrin, a pyrethroid chemical, is widely used as a pesticide because of its rapid insecticidal activity. Although permethrin is considered to exert very low toxicity in mammals, the effects of early, low‐level, chronic exposure on the adult central nervous system are unclear. In this study, we investigated the effects of low‐level, chronic permethrin exposure in early life on the brain functions of adult mice, using environmentally relevant concentrations. We exposed mice to the acceptable daily intake level of permethrin (0.3 ppm) in drinking water during the prenatal and postnatal periods. We then examined the effects on the central nervous system in adult male offspring. In the permethrin group, we detected behavior that displayed incomplete adaptation to a novel environment, as well as an impairment in learning and memory. In addition, immunohistochemical analysis revealed an increase in doublecortin‐ (an immature neuron marker) positive cells in the hippocampal dentate gyrus in the permethrin exposure group compared with the control group. Additionally, in the permethrin exposure group there was a decrease in astrocyte number in the hilus of the dentate gyrus, and remaining astrocytes were often irregularly shaped. These results suggest that exposure to permethrin at low levels in early life affects the formation of the neural circuit base and behavior after maturation. Therefore, in the central nervous system of male mice, low‐level, chronic permethrin exposure during the prenatal and postnatal periods has effects that were not expected based on the known effects of permethrin exposure in mature animals. Abstract : Permethrin is widely used as a pyrethroid pesticide. Although permethrin is considered to exert low mammalian toxicity, the effects of acceptable daily intake level and chronic exposure in early life are unclear. We investigated whether permethrin exposure in early life could exert effects on the brain functions of adult mice, using environmentally relevant concentrations. Our findings suggest that exposure to permethrin at low levels in early life affects the formation of the neural circuit base and behavior after maturation.